2020
DOI: 10.1002/jcla.23460
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular identification of mycoplasma pneumoniae associated with respiratory infections in Zhejiang province, China, 2008‐2017

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
7
2
Order By: Relevance
“…In addition, the positive rate of MP was detected more commonly in children 3 years of age or older than in younger children, which was corroborated by previous epidemiological studies ( Jain et al., 2015 ; Schildgen et al., 2018 ; Liu et al., 2020 ). However, the positive rate of MP in our study is different from that in other previous studies ( Gao LW et al., 2019 ; Jiang et al., 2020 ), which may be due to differences in MP detection methods and enrolled populations. Chemiluminescence was used to detect IgM antibodies of serum MP in our study, whereas atypical pathogen DNA was detected in nasopharyngeal samples by a polymerase chain reaction in some studies ( Del Valle-Mendoza et al., 2017 ; Jiang et al., 2020 ; Kumar et al., 2020 ), or MP antibody was detected by the passive agglutination method ( Gao CH et al., 2019 ; Gao LW et al., 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the positive rate of MP was detected more commonly in children 3 years of age or older than in younger children, which was corroborated by previous epidemiological studies ( Jain et al., 2015 ; Schildgen et al., 2018 ; Liu et al., 2020 ). However, the positive rate of MP in our study is different from that in other previous studies ( Gao LW et al., 2019 ; Jiang et al., 2020 ), which may be due to differences in MP detection methods and enrolled populations. Chemiluminescence was used to detect IgM antibodies of serum MP in our study, whereas atypical pathogen DNA was detected in nasopharyngeal samples by a polymerase chain reaction in some studies ( Del Valle-Mendoza et al., 2017 ; Jiang et al., 2020 ; Kumar et al., 2020 ), or MP antibody was detected by the passive agglutination method ( Gao CH et al., 2019 ; Gao LW et al., 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the positive rate of MP in our study is different from that in other previous studies ( Gao LW et al., 2019 ; Jiang et al., 2020 ), which may be due to differences in MP detection methods and enrolled populations. Chemiluminescence was used to detect IgM antibodies of serum MP in our study, whereas atypical pathogen DNA was detected in nasopharyngeal samples by a polymerase chain reaction in some studies ( Del Valle-Mendoza et al., 2017 ; Jiang et al., 2020 ; Kumar et al., 2020 ), or MP antibody was detected by the passive agglutination method ( Gao CH et al., 2019 ; Gao LW et al., 2019 ). PCR-based techniques are now considered more reliable, however, this method also has limitations, such as low sensitivity and positive predictive values ( Nilsson et al., 2008 ; Chang et al 2014 ; Kurkela et al 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although substantial numbers of children were diagnosed with M. pneumoniae infection throughout the study period, the epidemic peaked in the fourth quarter of each year between 2017 and 2019, which was consistent with the results obtained previously in South Korea [2,17], USA [3], Israel, and 11 countries of Europe [16]. However, the tendencies in these studies differ from the data reported in epidemiological studies in Italy [18], South Africa [19], and other regions of China [8,20,21]. The peaks of M. pneumoniae infection between 2017 and 2019 in our study coincided with the school semesters, and the number of infections fell significantly after schools were closed to limit the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…This may be related to the different epidemiological characteristics of the different respiratory pathogens in each region. From a single pathogen perspective, the high prevalence of with HBoV mixed with MP and HRV in this study may be related to the high prevalence of MP and HRV in summer and autumn in China ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 81%